COVID-19-Induced Anosmia and Ageusia Are Associated With Younger Age and Lower Blood Eosinophil Counts. Issue 6 (November 2021) - Sehanobish, Esha; Barbi, Mali; Fong, Valerie; Kravitz, Meryl; Sanchez Tejera, Denise; Asad, Mohammad; Matsumura, Cynthia; Ferastraoaru, Denisa; O'Neill, Meaghan; Karagic, Merhunisa; Akbar, Nadeem; Bottalico, Danielle M.; et al.
Background: Anosmia and ageusia are symptoms commonly associated with COVID-19, but the relationship with disease severity, onset and recovery are unclear. Objective: To examine factors associated with anosmia and ageusia and the recovery from these symptoms in an ethnically diverse cohort. Methods: Individuals tested for SARS-CoV-2 between March and April 2020 were eligible for the study. Randomly selected participants answered a telephone questionnaire on COVID-19 symptoms with a focus on anosmia and ageusia. Additionally, relevant past medical history and data on the COVID-19 clinical course were obtained from electronic medical records. 486 patients were in the COVID-19 group and 103 were COVID-19-negative. Results: Patients who were younger were more likely to report anosmia and/or ageusia (odds ratio (OR) for anosmia per 1-year increase in age: 0·98, 95%CI:0–97-0·99, p  = 0·003; for ageusia: 0·98, 95%CI:0·97-0·99, p  = 0·005) as were patients with lower eosinophil counts (OR for anosmia per 0.1-K/μL increase in eosinophils: 0·02, 95%CI:0·001-0·46, p  = 0·01, for ageusia 0·10, 95%CI:0·01-0·97, p  = 0·047). Male gender was independently associated with a lower probability of ageusia (OR:0·56, 95%CI:0·38-0·82, p  = 0·003) and earlier sense of taste recovery (HR:1·44, 95%CI:1·05-1·98, p  = 0·02). Latinos showed earlier sense of taste recovery than white patients (HR:1·82, 95%CI:1·05-3·18, p  = 0·03). Conclusion: Anosmia and ageusia were more common among younger patients and those with lower blood eosinophil counts. Ageusia was less commonly reported among men, and time to taste recovery was earlier among both men and Latinos.